2022
DOI: 10.3389/feart.2022.871902
|View full text |Cite
|
Sign up to set email alerts
|

Age-Heterogeneity in Marine Sediments Revealed by Three-Dimensional High-Resolution Radiocarbon Measurements

Abstract: Marine sedimentary archives are routinely used to reconstruct past environmental changes. In many cases, bioturbation and sedimentary mixing affect the proxy time-series and the age-depth relationship. While idealized models of bioturbation exist, they usually assume homogeneous mixing, thus that a single sample is representative for the sediment layer it is sampled from. However, it is largely unknown to which extent this assumption holds for sediments used for paleoclimate reconstructions. To shed light on 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Besides analytical precision, the beneficial effect of leaching is further limited by natural variability and sample heterogeneity. The standard deviation of the mean F 14 C values reported for young T. sacculifer replicate analyses greatly exceeded the analytical precision, highlighting that sample heterogeneity has a very large effect on the reliability of reported radiocarbon ages in line with findings by Dolman et al (2021) and Zuhr et al (2022). Dolman et al (2021) reported on replicate small-scale (3-30 tests of foraminifera) radiocarbon analyses and could show that due to bioturbation variance of the measured F 14 C means is a function of sample size (number of tests per sample) and sediment accumulation rate.…”
Section: Effect Of Leaching On Fossil Foraminiferasupporting
confidence: 73%
“…Besides analytical precision, the beneficial effect of leaching is further limited by natural variability and sample heterogeneity. The standard deviation of the mean F 14 C values reported for young T. sacculifer replicate analyses greatly exceeded the analytical precision, highlighting that sample heterogeneity has a very large effect on the reliability of reported radiocarbon ages in line with findings by Dolman et al (2021) and Zuhr et al (2022). Dolman et al (2021) reported on replicate small-scale (3-30 tests of foraminifera) radiocarbon analyses and could show that due to bioturbation variance of the measured F 14 C means is a function of sample size (number of tests per sample) and sediment accumulation rate.…”
Section: Effect Of Leaching On Fossil Foraminiferasupporting
confidence: 73%
“…Corrections from seasonally biased records have been suggested (e.g. Bova et al, 2021), but rely on assumptions that must be verified beforehand (Laepple et al, 2022).…”
Section: Limiting Factors From the Dataset And Future Developmentsmentioning
confidence: 99%
“…Even further, we should aim to quantitatively test our understanding of the proxy signal at different steps of the proxy formation. Replication inside one core allows to determine the variability due to measurement uncertainty and (sediment) archive heterogeneity (Zuhr et al., 2022). Comparison of different proxies for the same physical variable such as temperature measured in the same sample or core (Groeneveld et al., 2019; Ho & Laepple, 2015) allows to test the interpretation and attribution of the climate signal in the proxies.…”
Section: Main Textmentioning
confidence: 99%
“…Even further, we should aim to quantitatively test our understanding of the proxy signal at different steps of the proxy formation. Replication inside one core allows to determine the variability due to measurement uncertainty and (sediment) archive heterogeneity (Zuhr et al, 2022). Comparison of different The power spectral density of the tuned timeseries shows a clear peak at the annual frequency, whereas the original noise timeseries does not.…”
mentioning
confidence: 99%